قياس التعرضات الإشعاعية الناتجة عن التوضعات الفوسفاتية في المنطقة الساحلية (عين ليلون) - شويكاني, رياض; طنجور, زنان (Latakia University Journal -Biological Sciences Series, 2018)
This study included different measurements included phosphate depositions area of Ain Liloun area and around the coastal area and note if there are serious moral or for radon in houses that are studied in addition to estimating the dose experienced by families living in those Region Work included distribution of reactants to measure radon gas in homes randomly in area and around the coastal mountain range of revelations over checks on East and West Sea survey about 11 villages which reagents were distributed in two phases and included all phases of summer and winter period selected bedrooms To be a site measurement at home and adopted complementary way (accumulative) using nuclear impact detectors type CR-39, then processing the results using a stiodnt test (T-test) He found that the average radon concentration in houses was within normal limits and lower limits recommended by the ICRP 200Bq/m3 and showed no moral differences in radon concentrations between regions, and virtual high radon concentration in some areas was the result of special conditions such as the detector closed places poorly ventilated In some areas or the result of exceptional construction model with his foot or an affiliate of the social habits of the population. The study also found that homes that used stone material in their construction was the highest radon concentration of houses built from bricks and cement and increase in radon concentration in houses where the detector at ground level compared with the first floor. And show that the current population dose for highest concentration 2.0 mSv/y on the assumption that the entire area studied area appears, it goes down to 0.2 mSv/y then enter the actual space is less than public dose (1mSv/y) by the ICRP. تضمنت هذه الدراسة إجراء قياسات مختلفة شملت منطقة التوضعات الفوسفاتية منطقة عين ليلون وما حولها في المنطقة الساحلية، وملاحظة فيما إذا كان هناك تعرض أو خطورة ذات دلاله للرادون في المنازل التي خضعت للدراسة بالإضافة إلى تقدير الجرعة التي تتعرض لها العائلات القاطنة في تلك المنطقة. تضمن العمل توزيع كواشف لقياس غاز الرادون في المنازل بشكل عشوائي وبشكل يغطي منطقة التكشفات وما حولها من سلسلة الجبال الساحلية شرقاً وحتى البحر غرباً، وشملت الدراسة حوالي 11 قرية وتم توزيع الكواشف فيها على مرحلتين وتضمنت كل من المرحلتين فترة صيف وشتاء، واختيرت غرف النوم لتكون موقع القياس في المنزل، واعتمدت الطريقة التكاملية (التراكمية) باستخدام كواشف الأثر النووي نوع CR-39، ثم جرت معالجة النتائج إحصائياً باستخدام اختبار استيودنت (T- test) وجد أن وسطي تركيز الرادون في المنازل كان ضمن الحدود الطبيعية وأقل من الحدود الموصى بها من قبل ICRP 200Bq/m3 ولم تظهر أي فروق ذات دلاله في تراكيز الرادون بين المناطق، وأن الارتفاع الظاهري لتركيز الرادون في بعض المناطق كان نتيجة لظروف خاصة كوضع الكاشف بأماكن مغلقة سيئة التهوية في بعض المناطق أو نتيجة طراز البناء المتميز بقدمه أو تابعاً لعادات السكان الاجتماعية. كما وجد في هذه الدراسة أن المنازل التي استخدمت مادة الحجر في بنائها كان تركيز الرادون فيها أعلى من المنازل المبنية من البلوك والإسمنت، ولوحظ ارتفاع في تركيز الرادون في المنازل التي وضع فيها الكاشف في الطابق الأرضي مقارنة مع الطابق الأول. وتبين بأن الجرعة الحالية للسكان بالنسبة للتراكيز العليا هي 2.0 mSv/y على افتراض أن كامل المنطقة المدروسة منطقة تكشفات، إلا أنها تنخفض إلى 0.2mSv/y بعد إدخال المساحة الفعلية وهي أقل من جرعة عموم الناس(1mSv/y) حسب الـ ICRP.